Shoshonean Peoples and the Overland Trails - Morgan, Dale L. (Utah State University, University Libraries, 2007)
This compilation of Dale Morgan's historical work on Indians in the Intermountain West focuses primarily on the Shoshone who lived near the Oregon and California trails.Three connected works by Morgan are included: First is his classic article on the history of the Utah Superintendency of Indian Affairs. This is followed by a previously unpublished history of early relations among the Western Shoshoni, emigrants, and the government along the California Trail. The book concludes with an important set of government reports and correspondence from the National Archives concerning the Eastern Shoshone and their leader Washakie. Morgan heavily annotated these for serial publication in the Annals of Wyoming. He also wrote a previously unpublished history of early relations among the Western Shoshone, emigrants, and the government along the California Trail.Morgan biographer Richard L. Saunders introduces, edits, and further annotates this collection. His introduction includes an intellectual biography of Morgan that focuses on the place of the anthologized pieces in Morgan's corpus. Gregory E. Smoak, a leading historian of the Shoshone, contributes an ethnohistorical essay as additional context for Morgan's work.